Implementasi Model Pembelajaran Multikultural Dalam Meningkatkan Toleransi Di Sekolah - Akmal Fawwazi, Reza; Roihan, Davik; Mubin, Nurul (Tashdiq: Jurnal Kajian Agama dan Dakwah, 2024)
The implementation of multicultural learning models in schools plays a crucial role in fostering tolerance among students. This model integrates the values of cultural, religious, and ethnic diversity into the curriculum and school activities, creating an inclusive and harmonious learning environment. Through methods such as cross-cultural discussions, the use of multicultural learning media, and extracurricular activities, students can understand and appreciate differences. Studies show that applying multicultural learning models not only enhances students' understanding of diversity but also shapes the tolerant character needed in society. Therefore, collaboration between teachers, students, and school authorities is essential for the successful implementation of this model.